The role of symbiotic to treat diarrhea in a critically ill Guillain-barre syndrome patient with morbid and type 2 diabetes mellitus : A case report - Beatrice Cynthia Walter; Steffi Sonia; Wina Sinaga; Lily Indriani Octovia (World Nutrition Journal, 2023)
Guillain-Barre Syndrome (GBS) is a serious post-infectious immune-mediated neuropathy, and the case is increasing every year, approximately 6 in 100.000 cases yearly. Several cases depend on mechanical ventilation (MV) and have diarrhea during treatment in the intensive care unit (ICU). This case report aims to describe the role of synbiotic supplementation in treating diarrhea in a GBS patient in intensive care unit (ICU).